2006
DOI: 10.1021/ma061642v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclolinear Poly(carbosilane)-g-poly(methyl methacrylate or styrene) Random Copolymers

Abstract: The cyclolinear polycarbosilane, (poly(1-hexyl-1,3-ditolyl-1,3-disilacyclobutane) poly(HDTDSCB)), which has tolyl groups attached to the main chain Si atoms, was prepared by ADMET polymerization with the second-generation Grubbs catalyst, and 10%, 5%, and 2% of the tolyl groups were brominated by reactions with N-bromosuccinimide. A series of well-controlled poly(methyl methacrylate) (PMMA) anions of 2.5K, 5K, and 10K molecular weight were introduced via the "grafting onto" strategy at low temperature to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…27 Nonetheless, the same ATRP graft-from approach (Scheme 6) was successfully applied to the tolyl-substituted cyclolinear polycarbosilane, [-{RSi(CH 2 ) 2 SiR}-(CH 2 ) 6 -] n poly-(hexyleneditolyldisilacyclobutane or HDTDSCB) (M n = 10 K; PDI = 1.9, Tg = -6 • C) to prepare a poly-(HDTDSCB)-g-PS graft copolymer, without appreciable ring-opening. 38 It was suggested that the absence of RO in this case could be due to the relatively low temperature for the ATRP reaction as compared to the initiation temperature for the CuBr-catalyzed DSCB RO and/or the stabilized nature of the radical site in ATRP, along with the low concentration of radical species.…”
Section: Graft Copolymers Obtained By Both Atrp and Graft-onto Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…27 Nonetheless, the same ATRP graft-from approach (Scheme 6) was successfully applied to the tolyl-substituted cyclolinear polycarbosilane, [-{RSi(CH 2 ) 2 SiR}-(CH 2 ) 6 -] n poly-(hexyleneditolyldisilacyclobutane or HDTDSCB) (M n = 10 K; PDI = 1.9, Tg = -6 • C) to prepare a poly-(HDTDSCB)-g-PS graft copolymer, without appreciable ring-opening. 38 It was suggested that the absence of RO in this case could be due to the relatively low temperature for the ATRP reaction as compared to the initiation temperature for the CuBr-catalyzed DSCB RO and/or the stabilized nature of the radical site in ATRP, along with the low concentration of radical species.…”
Section: Graft Copolymers Obtained By Both Atrp and Graft-onto Methodsmentioning
confidence: 91%
“…In the latter approach, a macrocyclic anion was prepared separately by controlled anionic polymerization and added to the randomly brominated poly-(HDTDSCB) (Scheme 7). 37,38 Due to the relatively basic character of the polystyrene anion, some ring opening of the disilacyclobutane moieties in the main chain of poly-(HDTDSCB) was evidenced in efforts to apply this "graft onto" strategy with 6% brominated poly-(HDTDSCB), even at -78 • C in THF or in cyclohexane. 38 On the other hand, successful grafting without appreciable ring-opening was achieved with the PMMA anion in THF as long as the temperature was maintained at -78 • C. In order to maintain an approximately Scheme 6 Preparation of a PMTSM-g-PS copolymer by a graft-onto procedure.…”
Section: Graft Copolymers Obtained By Both Atrp and Graft-onto Methodsmentioning
confidence: 99%
“…Soc. Rev., 2011, 40, 1404-1445 1435 the utility of ADMET for synthesising inorganic/organic hybrid polymers containing main group elements such as polycarbosilanes, 31,180,181,[184][185][186][187] poly(carbosiloxane)s, 188 polycarbogermanes, [189][190][191] polycarbostannanes, 190,192 polyferrocenes, 193,194 and transition metal-containing polymers. [195][196][197] Furthermore, organic polymers with pendant cyclophosphazene rings can be addressed as an example of the latter category of hybrid materials.…”
Section: Metal Containing Polymersmentioning
confidence: 99%
“…57 Polycarbosilane was grafted with poly(methyl methacrylate) (PMMA) or polystyrene (PS) to form random copolymers 23. 58 Molecular weights of the PMMA copolmers ranged from 17 000-19 000 g mol À1 (PDI = 2.1-5.0) whereas the styrene copolymers exhibited molecular weights from 13 000-20 000 g mol À1 (PDI = 2.2-2.6). Cationic, water soluble, conjugated polysilanes were prepared which exhibited blue-emission and were highly sensitive to quenching agents such as [Fe(CN) 6 ] 4making them attractive as sensors.…”
Section: Polysilanes Polygermanes Polystannanes Polycarbosilanes and ...mentioning
confidence: 99%